Interstitial mycosis fungoides - Miguel Augusto M. Pereira; Mayara Toledo; Breno Arkader; Luciana Pantaleão (Sociedade Brasileira de Patologia Clínica, 2021)
ABSTRACT Interstitial mycosis fungoides (IMF) is a rare variant of mycosis fungoides, a cutaneous T-cell non-Hodgkin's lymphoma. It is characterized by an interstitial dermal infiltrate of lymphocytes and histiocytes between collagen bundles. We report the case of a 54-year-old patient with pruritic hypochromic macules on the arms and forearms diagnosed with IMF. Special attention was given to the anatomopathological features that differentiate this entity from its differential diagnoses, such as inflammatory morphea, interstitial annular granuloma, and other variants of the mycosis fungoides itself. We also present a review of the literature on the classification of the IMF.